Penulisan Hadis Pada Masa Rasulullah SAW. - Anwar, Latifah (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
In Islam, Hadith becomes the second guidelines after Al-Quran, therefore, Moslem had done a lot of efforts to keep its authenticity. At the beginning of Muhammad prophecy, there was no any Hadith coding as like Al-Quran. The existence of Hadith narration in Prophet Muhammad era was still debated because of the two contradictory Hadith riwayah. One of them indicated the prohibition for Hadith narration, and other directed its approval which led Hadith narration. Compared with ummi group, in Prophet Muhammad era, only few of Prophet Muhammad companions were able to write. In accepting the Hadith narration, the companions relied on the memorization than writing. The majority of Hadith Preachers assumed that, Hadith had been written by the companions when Prophet Muhammad was still alive. Whereas, the orientalist and some of modern Moslem experts mentioned that Hadith had not been written in Prophet Muhammad era. Some of the companions had their own Hadith writing, although there were any contradictory Hadith between prohibition and approval in Hadith writing. Only few companions who wrote Hadith, such as ‘Abdullah Ibn ‘Amr Ibn ‘Al-Ash, allowed by Prophet Muhammad to write Hadith. Prophet Muhammad never instructed certain companion to write and compile Hadith as like Al-Quran which was officially written by Prophet Muhammad’s individual secretary, Zayd Ibn Tsabit. Whereas, the officially Hadith coding was started at Umar ibn ‘Abd al ‘Aziz era (99H – 101H).